OPTIMIZING THE ROLE OF CORRECTIONAL INSTITUTIONS IN FOSTERING PRISONERS WITH A BACKGROUND BACKGROUND - Muhammad Syahri Ramadhan (Polteknik Ilmu Pemasyarakatan, 2018)
Every a correctional institution is in each region indonesia would surely variegated in terms of any, Like for example is correctional institution for woman and children, where buildings correctional institution for both prisoners were built specifically to its own. But , the sometimes out of sight is that there are several prisoners in indonesia which has background disability. Development process it will also make the law office in criminal justice systems country can be realized with good. To provide training to convict moreover disability , should be understood that basic elements coaching convicts namely the inmate itself , the officers community elements to walk optimally.